A Study on Variation of Placental Index in Different Gestational Age Groups of Healthy Pregnant Mother of Bangladesh (KYAMC Journal, 2025)
Background: The placenta is an organ that is absolutely essential to the survival of the fetus. All the enabolites needed for fetal metabolism come from the mother’s blood and fetal catabolites are passed back into the mother’s circulation through the placenta. So, as a mirror, it reflects the intra-uterine status of the fetus.Objectives: This study was done to provide information about the placental index in different gestational ages of healthy pregnancies.Materials and Methods: This cross-sectional descriptive study was performed on 80 human placentas in the Department of Anatomy, Mymensingh Medical College, Mymensingh, from January to December 2018 of healthy Bangladeshi pregnant mother in relation to different gestational age. By purposive sampling technique the collected samples were divided into three gestational age groups. They were Group A (28 to 36 weeks), Group B (37 to 40 weeks) and Group C (above 40 weeks) and examined morphologically by fine dissection method. The placental index (placental coefficient) was calculated by dividing placental weight by the birth weight of the baby.Result: The mean (± SD) placental index was 0.17±0.09 in group A, 0.14±0.01 in group B and 0.15±0.03 in group C. It was also observed that the mean placental index decreased with gestational age up to a certain level then increased. The mean difference of the placental index between groups A and C was statistically moderately significant (p < 0.01) but the difference between groups A and B, B and C was statistically non-significant (p > 0.05). Conclusion: The present study showed an increase in birth weight will be followed by increased placental weight which is useful both clinicians and researchers for further studies to evaluate the correlation of placental index with pregnancy and neonatal outcome.KYAMC Journal. 2024; 15(02): 83-87